Konsep Dasar Evaluasi Dan Implikasinya Dalam Evaluasi Pembelajaran Pendidikan Agama Islam di Sekolah - Isropil Siregar; Hasbi Izzat; Muhammad Al Hafizh; Santi Wulandari (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Learning evaluation is an important component in the educational process that aims to determine the extent to which the success of the learning process has been achieved. In the context of Islamic Religious Education (Islamic education), evaluation not only assesses cognitive aspects, but also affective and psychomotor. This article discusses the basic concept of evaluation and its implications in evaluating Islamic education learning in schools. Through a literature review, this paper emphasizes the importance of a comprehensive understanding of evaluation to produce an effective Islamic education learning process.